The Effect Of Services Marketing Mix Elements On Customer-Based Brand Equity: An Empirical Study On Mobile Telecommunication Service In Indonesia - Rusdianto, Ashwin Hendik, Dr. Ihwan Susila, SE., M.Si (2016)
This paper explores the effect of services marketing mix elements on customer-based brand equity through empirical study of mobile telecommunication service in Indonesia. This study aims to determine the influence of such elements on customer-based brand equity and to reveal which is the most influential. Data were collected using questionnaire-based survey consisting of 50 questions and distributed to 120 respondents comprising all of Indonesian mobile telecommunication consumer in Indonesia city Solo and Madiun. In order to analyze the data obtained from questionnaires, quantitative methods were employed. The findings showed that service marketing mix elements togetherness have a significant effect on customer-based brand equity dimensions i.e. brand awareness, brand image, perceived quality and brand loyalty. Finally, the study recommends that management should improve the marketing mix elements by applying the right mix to gain high customer-based brand equity in order to be more competitive.